38th AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2002
DOI: 10.2514/6.2002-4261
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulations of Ion Thruster Accelerator Grid Erosion

Abstract: The highly successful demonstration of ion propulsion on Deep Space 1 has stimulated the study of more demanding applications of ion propulsion. These future applications require ion thrusters capable of providing significantly greater specific impulses and total impulses than the current state-of-the-art Higher specific impulses aggravate the known wear out mechanisms of the ion accelerator system. Computer simulations of the ion accelerator system operation and erosion are essential tools for the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…That is, when a single ion with a particular energy bombards the grid surface, it will produce a certain number of atoms or sputtering, and the unit is / n ion or / g ion. The amount of sputtering yield is calculated by the preset number of iterations, and sputtering yield is calculated according to the fitting formula given by Rosenberg, Brophy and Yim et al [22][23][24].…”
Section: R E F Ref Erefmentioning
confidence: 99%
“…That is, when a single ion with a particular energy bombards the grid surface, it will produce a certain number of atoms or sputtering, and the unit is / n ion or / g ion. The amount of sputtering yield is calculated by the preset number of iterations, and sputtering yield is calculated according to the fitting formula given by Rosenberg, Brophy and Yim et al [22][23][24].…”
Section: R E F Ref Erefmentioning
confidence: 99%
“…The distribution of ion density in the upstream region of the grids is an important boundary condition for obtaining the ion extraction characteristics using the numerical calculation method. Some references [7,9] have indicated that an overperveance condition and an under-perveance condition occur when the upstream plasma density is at a higher level and a lower level, respectively. as equation (4), which only changes the density of the different particle types.…”
Section: Ion Density In the Upstream Of The Gridsmentioning
confidence: 99%
“…ions tend along single ion trajectory paths [15]. Therefore, for a beam flatness based on the ion flux of ions of all charges we use…”
Section: Beam Flatness (Grid Performance and Utilization)mentioning
confidence: 99%
“…Performance effects due to double ion content. Double ions typically hurt thruster performance since they require nearly twice the electron energy to create as single ions, accelerate wear mechanisms and deliver reduced thruster per unit of ion current [15,17,18]. Consequently, discharge chambers should be designed to minimize double ionization to avoid these performance losses.…”
Section: Beam Flatness (Grid Performance and Utilization)mentioning
confidence: 99%